2017
DOI: 10.4049/jimmunol.1602020
|View full text |Cite
|
Sign up to set email alerts
|

CXCL4 Exposure Potentiates TLR-Driven Polarization of Human Monocyte-Derived Dendritic Cells and Increases Stimulation of T Cells

Abstract: Chemokines have been shown to play immune-modulatory functions unrelated to steering cell migration. CXCL4 is a chemokine abundantly produced by activated platelets and immune cells. Increased levels of circulating CXCL4 are associated with immune-mediated conditions, including systemic sclerosis. Considering the central role of dendritic cells (DCs) in immune activation, in this article we addressed the effect of CXCL4 on the phenotype and function of monocyte-derived DCs (moDCs). To this end, we compared inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 78 publications
7
45
0
Order By: Relevance
“…Several pathways involved in inflammatory responses 123 such as TLR signaling, interferon signaling, and cytokine signaling, were significantly 124 upregulated in CXCL4-moDCs compared to conventional moDCs (Figure 1-figure 125 supplement 2E). Confirming our previous findings (Silva-Cardoso et al, 2017), these 126 transcriptional changes were followed by increased production of pro-inflammatory mediators 127 such as IL-1β, IL-6, IL-12, IL-23, IL-27, TNF and CCL22, and down-regulation of immune-128 suppressive mediator CCL18 (validated using Luminex assays; see Figure 1J-K and Figure 1-129 figure supplement 2A-D). Pathways involved in cellular adhesion, integrin signaling, ECM 130 organization, and collagen formation, among others, were upregulated in CXCL4-moDCs upon 131 polyI:C stimulation compared to stimulated moDCs (Figure 1-figure supplement 2E), 132 indicating that CXCL4 exposure induces a pro-inflammatory and pro-fibrotic phenotype.…”
supporting
confidence: 82%
“…Several pathways involved in inflammatory responses 123 such as TLR signaling, interferon signaling, and cytokine signaling, were significantly 124 upregulated in CXCL4-moDCs compared to conventional moDCs (Figure 1-figure 125 supplement 2E). Confirming our previous findings (Silva-Cardoso et al, 2017), these 126 transcriptional changes were followed by increased production of pro-inflammatory mediators 127 such as IL-1β, IL-6, IL-12, IL-23, IL-27, TNF and CCL22, and down-regulation of immune-128 suppressive mediator CCL18 (validated using Luminex assays; see Figure 1J-K and Figure 1-129 figure supplement 2A-D). Pathways involved in cellular adhesion, integrin signaling, ECM 130 organization, and collagen formation, among others, were upregulated in CXCL4-moDCs upon 131 polyI:C stimulation compared to stimulated moDCs (Figure 1-figure supplement 2E), 132 indicating that CXCL4 exposure induces a pro-inflammatory and pro-fibrotic phenotype.…”
supporting
confidence: 82%
“…3B), but not with pDCs or B cells. Previous data from others and our group indicate clear immunomodulatory effects of CXCL4 at higher doses [21,22]. In co-culture with monocytes, increasing amount of CXCL4 up to 5 μg/mL did not additionally enhance the IL-17 induction (Supporting Information Fig.…”
Section: Cxcl4 Induces Il-17 Production By Cd4 + T Cells When Co-cultmentioning
confidence: 57%
“…Previous works have shown that during monocyte differentiation into dendritic cell or macrophage, the addition of CXCL4 resulted in an altered expression of cell surface markers and a distinct transcriptomic profile . They also differed in their capacity to activate T cells, yet the effect on IL‐17 production was not assessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods: We differentiated human moDCs in the presence of CXCL4. After 6 days differentiation, cells were stimulated with a TLR3 ligand (polyI:C) as described in our previous study 2. RNA sequencing and DNA methylation profiling was performed at various time points during differentiation and stimulation.…”
mentioning
confidence: 99%